Bias Testing of Mechanical Sampling System Based on Total Moisture and Ash Analysis - Ichsan, A Muhammad Nur; Irviansyah, Alfian (Journal of Chemical Process Engineering, 2024)
As one of the energy sources utilized in various industries, coal quality is determined by its maceral composition, mineral matter, and coalification rank. Generally, coal quality can be assessed through proximate and ultimate analyses conducted in laboratories. Coal samples can be collected from various locations, such as moving streams or stationary setups, using either manual or mechanical systems. In this study, a bias test was conducted on a mechanical sampling system. Bias is detected as the difference between test results and accepted reference values. The acceptability of reference values is established through simultaneous coal sampling using both the reference method and the system under testing. Bias testing is required for new installations, system relocations, system upgrades or modifications, and system maintenance. The procedure involves several stages, including pre-bias inspection, bias inspection, sample analysis, statistical analysis, and data interpretation. A total of 30 paired samples were analyzed, with the parameters measured being total moisture and ash content. These parameters were mathematically processed to calculate the Hotelling’s T² value, which was then compared to the T0² value to determine the presence or absence of bias. The results of the study indicated that the T² value was 4.425, while the T0² value for n = 30 and p = 2 was 6.885. This demonstrates that no bias was detected in the mechanical sampling system, as T² < T0².